Evaluation of a digital remote extraction analysis and monitoring tool for key performance indicators (KPIs) in the blood culture process - Claudio Palmieri; Laura Bartolini; Andrea Berlingeri; Barbara Camilloni; Gianfranco La Bella; Michela Pascarella; Marina Selleri; Felice Valzano; Chiara Vismara; Simone Ambretti; Carla Fontana; Mario Rassu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)
Purpose Bloodstream infections (BSIs) pose a significant health threat, requiring effective diagnostic processes to ensure appropriate treatment. Monitoring the quality of blood cultures (BCs) process (the cornerstone of BSIs etiological diagnosis) is critical. This study aimed to describe an automated tool, BD DREAM™ (Digital Remote Extraction Analysis & Monitoring), designed for monitoring key performance indicators (KPIs) in the BCs process. Methods A multicenter study was conducted across six Italian hospitals, analyzing 234,978 BC bottles, associated with 55,819 episodes. The system monitored KPIs related to mean blood volume per bottle, rates of solitary episodes, rate of BCs from central venous catheter (CVC) unpaired with concomitant BCs from peripheral vein, and contamination rates. Results The findings highlighted significant variability in BC practices among centers and hospital services, with mean blood volume per bottle below recommended standards (6.45 mL vs. ≥ 8.0 mL), with 21.8% (range 3.2–62.9%) of episodes classified as solitary. The rate of BCs from CVC unpaired with concomitant BCs from peripheral vein was 14.9% (range 10.2–39.0%). Overall, contamination rates ranged from 4.2 to 4.7%, depending on the criteria adopted for definition. The setting with the more critical values was medical area. Conclusion The tool was useful for immediate visualization and identification of hospital services with critical performance. These results suggest that integrating BC digital monitoring tools into clinical microbiology workflows is possible. Further studies will be needed to demonstrate that the implementation of BD DREAM™ can lead to enhancement of diagnostic accuracy, optimization of resources allocation, and improvement of patient outcomes.

Long-acting injectable risperidone and metabolic ratio: a possible index of clinical outcome in treatment-resistant schizophrenic patients - Lucia Sara Volonteri; Giancarlo Cerveri; Ilaria Francesca De Gaspari; Maria Luisa Baldi; Maria Laura Rolandi; Pietro Papa; Massimo Carlo Mauri; Claudio Mencacci (Psychopharmacology, 2010)